2022
DOI: 10.3847/2041-8213/ac5faf
|View full text |Cite
|
Sign up to set email alerts
|

A Disk Instability Model for the Quasi-periodic Eruptions of GSN 069

Abstract: GSN 069 is a recently discovered quasi-periodic eruption (QPE) source recurring about every 9 hr. The mechanism for the QPEs of GSN 069 is still unclear. In this work, a disk instability model is constructed to explain GSN 069 based on Pan et al. (PLC21), where the authors proposed a toy model for the repeating changing-look active galactic nuclei. We improve the work of PLC21 by including a nonzero viscous torque condition on the inner boundary of the disk and adopting a general form for the viscous stress to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Although enough flares have been seen in a number of cases for the mean period to be fairly well determined (as many as 15 in eRO-QPE1: Arcodia et al 2021), in all cases the interflare intervals fluctuate by modest amounts, hence the adjective "quasiperiodic." Since the first example was published a few years ago, numerous mechanisms have been suggested to explain these enigmatic events: self-lensing of a pair of supermassive black holes (Ingram et al 2021), accretion disk instability (Pan et al 2022), interactions between stars and accretion disks (Suková et al 2021;Xian et al 2021), and a number of variations on tidal stripping of nearby stars by supermassive black holes (King 2022;Linial & Sari 2022;Metzger et al 2022;Wang et al 2022;Zhao et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Although enough flares have been seen in a number of cases for the mean period to be fairly well determined (as many as 15 in eRO-QPE1: Arcodia et al 2021), in all cases the interflare intervals fluctuate by modest amounts, hence the adjective "quasiperiodic." Since the first example was published a few years ago, numerous mechanisms have been suggested to explain these enigmatic events: self-lensing of a pair of supermassive black holes (Ingram et al 2021), accretion disk instability (Pan et al 2022), interactions between stars and accretion disks (Suková et al 2021;Xian et al 2021), and a number of variations on tidal stripping of nearby stars by supermassive black holes (King 2022;Linial & Sari 2022;Metzger et al 2022;Wang et al 2022;Zhao et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is an inconsistency between the model predictions and the observational data (Arcodia et al 2021). Pan et al (2022) suggested that the radiation-pressure instability model can explain the QPEs if a nonzero viscous torque condition is included on the inner boundary of the disk. This model can explain the QPEs in active galaxies, but it has difficulty explaining the QPEs that are observed in lowluminosity active galactic nuclei (AGNs; e.g., eRO-QPE1/2, Wevers et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…An alternative class of models are based on possible instabilities in the BH accretion disk (Miniutti et al 2019;Sniegowska et al 2020;Pan et al 2022;Raj & Nixon 2021). The simplest version of this, based on thermal-viscous instability (Lightman & Eardley 1974), is disfavored by detailed modeling of the X-ray lightcurves (Arcodia et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The simplest version of this, based on thermal-viscous instability (Lightman & Eardley 1974), is disfavored by detailed modeling of the X-ray lightcurves (Arcodia et al 2021). More complex models (e.g., Pan et al 2022;Raj & Nixon 2021), with more free parameters (describing the viscous torques, magnetic pressure, size of the unstable zones, spin-disk misalignment, etc.) are potentially viable for some QPEs that are in bright, long-lived active galac-Figure 1.…”
Section: Introductionmentioning
confidence: 99%